ON THE QUESTION OF RESTORATION OF SENSITIVITY TO GLUCO-CORTICOIDS WITH OMALIZUMAB IN BRONCHIAL ASTHMA - Suvarov A. A.; Khatamov K. M.; Kireev V. V.; Ochilov S. I. (Modern American Journals, 2025)
Objective of the study: to investigate the effect of omalizumab on the sensitivity to glucocorticoids in asthma. Materials and methods: 15 patients with asthma at stages III and IV were examined. The determination of sensitivity to glucocorticoids was carried out using a patented original method for assessing sensitivity to glucocorticoids (hydrocortisone, prednisolone, methylprednisolone, dexamethasone, triamcinolone, betamethasone). The principle of the method is based on the sensitivity of lymphocytes to glucocorticoids. If the number of lymphocytes after incubation with glucocorticoid solutions decreased by 1-20%, the sensitivity result is assessed as very low sensitive; 21-40% - low sensitive; 41-60% - sensitive; 61-80% - highly sensitive; over 80% - very highly sensitive. All patients underwent assessment of glucocorticoid sensitivity in peripheral blood before and after 4 weeks. Results and conclusions: 1. Against the background of omalizumab treatment, there is an increase in the degree of very high sensitivity to betamethasone by 1.18 times, to prednisolone by 1.37 times, and to hydrocortisone by 2.6 times. 2. A decrease in very high sensitivity to methylprednisolone by 1.8 times, to dexamethasone by 1.2 times, and to triamcinolone by 1.08 times is observed.
Keywords: omalizumab, sensitivity to glucocorticoids, bronchial asthma, prednisolone, dexamethasone, hydrocortisone, methylprednisolone, betamethasone.